THE SCIENCE OF EDUCATION AND ITS RELEVANCE TO EDUCATIONAL RESEARCH: CONTRIBUTIONS TOWARDS A SUSTAINABLE SOCIETY - de Alencar, Adna Rodrigues; Castro, Argentina Mororó; Soares, Danielle Taumaturgo Dias; de Oliveira, Emanuelle Grace Kelly Santos; Filho, Ivan de Oliveira Holanda; Ferreira, Jayane Freires; Junior, Juvanildo Terra de Alencar; Pereira, Jeckson Rubens Macedo de Lima; Amaral, Lilian do Socorro Viana e Viana; da Cruz, Marcos Paulo Mesquita; Xavier, Régia Maria Carvalho; Gomes, Rickardo Léo Ramos (Seven Editora, 2024)
The article "The Science of Education and its Relevance to Educational Research: Contributions Towards a Sustainable Society" explores the importance of the Science of Education in shaping pedagogical practices that promote social and environmental sustainability. In a context where education is viewed as a fundamental pillar for the development of critical and engaged citizens, educational research becomes an essential tool for understanding and implementing these practices. The study highlights how the Science of Education can integrate diverse theories and methodologies, contributing to the construction of a more conscious and responsible education. The methodology adopted followed a qualitative approach, utilizing bibliographic research to analyze relevant works and theories in the field. The general objective was to investigate the relevance of the Science of Education to educational research, emphasizing its contributions to the promotion of a sustainable society. To this end, specific objectives were established, addressing topics ranging from the analysis of the characteristics of educational research to discussions on normativity and pedagogical practice. In conclusion, the Science of Education proves to be an essential discipline in the search for educational solutions that promote not only knowledge but also the ethical and social values necessary to face contemporary challenges. By integrating theory and practice, this science significantly contributes to the development of individuals committed to a more sustainable future, reaffirming its central role in educational research. DOI:https://doi.org/10.56238/sevened2024.021-005